2002
DOI: 10.22358/jafs/67812/2002
|View full text |Cite
|
Sign up to set email alerts
|

Studies on N-metabolism in different gastrointestinal sections of sheep using the digesta exchange technique. 3. N secretion and reabsorption

Abstract: Using a combination of fistulation, l5 N isotope technique and digesta exchange between labelled and unlabelled sheep, the flow rates of digesta (Sandek et al., 2001a) and the flow rates of endogenous N (Sandek et al., 2001b) were previously estimated. On the basis of these data N reabsorption in the stomachs, the small and large intestine as well as N secretion in these three sections were calculated and differences caused by variations in the crude fibre intake of the two feeding groups (Group 1: 89.7 g/d, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There was evidence of urea degradation in the large intestine posterior to the caecum, and it was suggested that urea degradation and absorption of the synthesized NH 3 might also occur in the ileum. Kowalczyk et al (1975a,b) stated that only a small amount of blood urea nitrogen was utilized for microbial synthesis in the rumen, and the greatest part of postruminal endogenous nitrogen was reabsorbed during passage of digesta through the intestine (Sandek et al, 2002). Norton et al (1978) noted that an average of 81% of the urea synthesized in the body was transferred to the digestive tract and degraded to NH 3 and carbon dioxide.…”
Section: Urea Degradation In the Reticulorumen And Post-ruminal Digesmentioning
confidence: 99%
See 1 more Smart Citation
“…There was evidence of urea degradation in the large intestine posterior to the caecum, and it was suggested that urea degradation and absorption of the synthesized NH 3 might also occur in the ileum. Kowalczyk et al (1975a,b) stated that only a small amount of blood urea nitrogen was utilized for microbial synthesis in the rumen, and the greatest part of postruminal endogenous nitrogen was reabsorbed during passage of digesta through the intestine (Sandek et al, 2002). Norton et al (1978) noted that an average of 81% of the urea synthesized in the body was transferred to the digestive tract and degraded to NH 3 and carbon dioxide.…”
Section: Urea Degradation In the Reticulorumen And Post-ruminal Digesmentioning
confidence: 99%
“…Urea-N entering the digestive tract that was returned to the ornithine cycle remained constant across intakes but the absolute amount increased with N intake. Urea removed by the PDV, unaffected by intake, represented 32, 33, and 21% of the digested N. Meanwhile the reabsorption of endogenous nitrogen was signifi cantly infl uenced by the dietary crude fi bre level for growing sheep (Sandek et al, 2002). Leng and Nolan (1984) reported that NH 3 concentrations in rumen fl uid were positively correlated with the number of ciliate protozoa, and NH 3 concentrations in the rumen fl uid of defaunated animals were lower than in those with protozoa.…”
Section: Urea Degradation In the Reticulorumen And Post-ruminal Digesmentioning
confidence: 99%
“…No difference could be observed in N flux, protein synthesis, protein breakdown or in the reutilization rate of N. However, the fractional growth rate (FGR) and the efficiency of protein synthesis (N balance/synthesis x 100) were significantly greater in Group 1 (PO.10). In this Group fed a diet with a lower CF content, N secretion in the small intestine was significantly (P<0.10) lower than in Group 2 given a diet with a higher CF content (9.4 vs 16.0 g N x kg DMT 1 ; Sandek et al, 2002).…”
Section: Resultsmentioning
confidence: 64%
“…The higher the intestinal N secretion, the lower the efficiency of protein synthesis (N balance/synthesis). The N secretion is stimulated by dietary factors, like crude fibre content (Sandek et al, 2002) or intestinal passage of NDF (Zebrowska and Kowalczyk, 1991;Lammers-Wienhoven et al, 1998). Under practical feeding conditions this loss by N secretion should be take into account in protein evaluation systems for ruminants as indirectly done in the energy evaluation systems with the factor q (Van Es, 1975).…”
Section: Discussionmentioning
confidence: 99%